(untitled) (Journal on Excellence in College Teaching, 2024)
In the 38-year history of faculty learning communities (FLCs), there have been just a few unsuccessful attempts at implementing an FLC on a particular topic or for a certain cohort. This may have occurred, for example, because of failure to obtain the necessary membership numbers. As stated in the FLC definition, these numbers are 6-15, with 8-12 recommended (Cox, 2004). If this failure happens over time, then having an FLC on that topic or for that cohort seems impossible. Modifying the structure of an FLC by altering its definition or omitting some of the 30 FLC components (Cox, 2002, 2004) is one way of attempting to address the design and implementation of an FLC that has proved impossible. In addition to the FLC definition and components, there are 16 recommendations that, in general, guide designing, implementing, and sustaining FLCs and FLC Programs (Cox, 2016). When helpful, I encourage FLC modifications and adaptations in order to accommodate institutional culture and meet the challenge or opportunity to be addressed. In this issue of the Learning Communities Journal, our authors confront FLC extremes and report their FLC designs and implementations, some that do not involve FLC modifications and some that do.